Razlike v izboru prostočasne športne dejavnosti pred epidemijo COVID-19 v Sloveniji in med njo - Kuraj, Jaka (Šport (Ljubljana), 2021)
The aim of this study was to investigate the most popular leisure-time sport activities among Slovenian population and impact of COVID-19 restrictions on their selection. In analysis were included 297 persons aged between 18 and 65, who filled in a whole questionnaire (average age 28,8 +- 12,75year). The results show that Slovenes most preferred leisure-time sport activity is still walking. Home workout and walking are the most frequent substitute for "forbidden" leisure- time sport activities during epidemic.
Keywords: COVID-19; epidemic; epidemije; leisure-time sport activities; physical activity; prostočasne športne dejavnosti; Slovenci; Slovenes; sport; šport; telesna dejavnost